In vitro strategies for the enhancement of secondary metabolite production in plants: a review - Fazili, Mohammad Afaan (2023)
Plants are the prime source of vital secondary metabolites (SMs) which are medicinally important for drug development, and these secondary metabolites are often used by plants in the various important tasks like defense against herbivory, interspecies defenses and against different types of stresses. For humans, these secondary metabolites are important as medicines, pigments, flavorings and drugs. Because most of the pharmaceutical industries are highly dependent on medicinal plants and their extraction, these medicinal plants are getting endangered.